2016
DOI: 10.1002/jhm.2656
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a multicenter performance improvement program for early detection and treatment of severe sepsis in general medical–surgical wards

Abstract: Sepsis is a leading cause of in‐hospital death, and evidence suggests a higher mortality in patients presenting with sepsis on the ward compared to those presenting to the emergency department. Ward patients who develop severe sepsis may have poor outcomes for a variety of reasons, including delayed diagnosis, lack of readily available staffing, and delayed treatment. We report on a multihospital quality improvement program for early detection and treatment of sepsis on general medical–surgical wards. We descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 13 publications
1
36
0
3
Order By: Relevance
“…In this issue of the Journal of Hospital Medicine, we examine early detection from various perspectives but around a common theme that usually gets less attention in the academic literature: implementation. The article by Schorr et al 23 describes a disease-specific approach that can be instantiated using either electronic or paper tools. Escobar et al 24 describe the quantitative as well as the electronic architecture of an early warning system (EWS) pilot at 2 hospitals that are part of an integrated healthcare delivery system.…”
Section: Articles In This Issuementioning
confidence: 99%
“…In this issue of the Journal of Hospital Medicine, we examine early detection from various perspectives but around a common theme that usually gets less attention in the academic literature: implementation. The article by Schorr et al 23 describes a disease-specific approach that can be instantiated using either electronic or paper tools. Escobar et al 24 describe the quantitative as well as the electronic architecture of an early warning system (EWS) pilot at 2 hospitals that are part of an integrated healthcare delivery system.…”
Section: Articles In This Issuementioning
confidence: 99%
“…Quality improvement programs implemented at individual health systems have improved outcomes for patients with sepsis. 9 , 10 However, overall compliance with recommended treatment remains poor. Deep learning is a suite of novel machine learning methods that have achieved performance on many challenging tasks.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely demonstrated that management and clinical outcomes in patients presenting bacteraemia improve when infectious diseases specialists participate 15. Furthermore, interventions on patients with sepsis have also been shown to be effective in terms of clinical results 16. However, no literature can be found focused specifically on ASP interventions in patients with negative BCx.…”
Section: Discussionmentioning
confidence: 99%